Projected response of global runoff to El Niño-Southern oscillation - Thanh Le; Kyung-Ja Ha; Deg-Hyo Bae (Environmental Research Letters, 2021)
The El Niño-Southern Oscillation (ENSO) is a major mode of interannual climate variability and is expected to affect runoff variations at a global scale. While previous studies focused on the correlation analysis between ENSO and runoff and ENSO-induced amplitude changes of runoff, causal analysis considering the confounding impacts of other major climate modes is lacking. As more extreme ENSO events are projected in the future, it is crucial to enhance our understanding of the impacts of ENSO on global runoff. Here we examine the causal influences of ENSO on runoff over the future period 2015–2100 using outputs from Coupled Modeling Intercomparison Project Phase 6 model simulations. Our analyses account for the possible confounding effects of the Southern Annular Mode, the North Atlantic Oscillation and the Indian Ocean Dipole. We find that the signature of ENSO is detectable in future total runoff over various regions including limited areas in central and eastern Asia, large parts of Southeast Asia, limited areas in the eastern and southern Africa, western and eastern Australia, parts of southern and western North America, eastern Antarctica and large parts of South America. There is a high agreement across models for the causal influences of ENSO over central Asia, the eastern coast of Australia, southcentral North America and South America. Multi-model future projections demonstrate higher impacts of ENSO on total runoff over western and central Asia, the western coast of North America and southeastern South America compared to the historical period 1915–2000. All regions with substantial ENSO impacts account for 3.6% land-area in historical simulation and this fraction increases to 5.6% in the future scenario. In addition, the results underscore that surface runoff is less sensitive to ENSO compared to total runoff in most regions. These results may have implications for future water management planning based on ENSO.